Mechanisms of macular edema - Haydinger, Cameron D.; Ferreira, Lisia Barros; Williams, Keryn A.; Smith, Justine R. (Frontiers in Medicine, 2023)
Macular edema is the pathological accumulation of fluid in the central retina. It is a complication of many retinal diseases, including diabetic retinopathy, retinal vascular occlusions and uveitis, among others. Macular edema causes decreased visual acuity and, when chronic or refractory, can cause severe and permanent visual impairment and blindness. In most instances, it develops due to dysregulation of the blood-retinal barrier which permits infiltration of the retinal tissue by proteins and other solutes that are normally retained in the blood. The increase in osmotic pressure in the tissue drives fluid accumulation. Current treatments include vascular endothelial growth factor blockers, corticosteroids, and non-steroidal anti-inflammatory drugs. These treatments target vasoactive and inflammatory mediators that cause disruption to the blood-retinal barrier. In this review, a clinical overview of macular edema is provided, mechanisms of disease are discussed, highlighting processes targeted by current treatments, and areas of opportunity for future research are identified.